Remarkable in vitro anti-HIV activity of new silver(I)– and gold(I)–N-heterocyclic carbene complexes. Synthesis, DNA binding and biological evaluation. (28th May 2016) - Sánchez, Oriel; González, Sorenlis; Higuera-Padilla, Ángel R.; León, Yokoy; Coll, David; Fernández, Mercedes; Taylor, Peter; Urdanibia, Izaskun; Rangel, Héctor R.; Ortega, Joseph T.; Castro, William; Goite, María Cristina
Abstract : Graphical abstract: Two novel complexes of silver and gold with 2, 6-bis(3-methylimidazolin-2-yliden-1-yl)pyridine dibromide were synthesized and characterized. Their biological activities were evaluated through of the binding to CT DNA and inhibition in tumor cell lines and MT4 cells infected with HIV-1. Inhibition of the viral activity was over 55% at low concentrations. Abstract: A novel metallomacrocyclic silver complex [Ag(C13 H13 N5 )]2 Br2 1 and a bimetallic bridged gold complex [Au2 (C13 H13 N5 )Cl2 ]2 derived from 2, 6-bis(3-methylimidazolin-2-yliden-1-yl)pyridine dibromideL1 have been synthesized and fully characterized by UV–Vis, elemental analysis, FT-IR, NMR techniques and DFT calculations. The DNA interactions with the compounds were investigated by UV-spectrophotometric studies, viscosity measurements and DNA electrophoresis. Additionally, the lipophilicity values were determined from the water/ n -octanol partition coefficient. Experimental data indicated that all the compounds interacted with DNA, through a non-covalent binding mode.L1 and2 were found to be hydrophilic character while1 was somewhat lipophilic. The biological activities ofL1, 1 and2 were tested against a panel of cancer cell lines (MCF-7, PC-3, A459, HeLa, HT-29 and the 4T1 murine tumor cell line). In vitro antiviral studies against HIV-1 were performed in infected MT4 leukemia cells. All the compounds exhibited a low activity against the cell lines, associated possibly with low lipophilicity values. However, complexes1 and2 showed remarkable viral inhibition at low concentrations. The complexes may inhibit virus infectivity through interaction with the HIV-1 envelope proteins.